The token's secret: the two-faced financial incentive of the token economy - Benedict J. Drasch; Gilbert Fridgen; Tobias Manner-Romberg; Fenja M. Nolting; Sven Radszuwill (Electronic Markets, 2020)
Multi-sided platforms are omnipresent in today's digital world. However, establishing a platform includes challenges: The platform utility usually increases with the number of participants. At an early stage, potential participants expect the platform utility to be low and lack an incentive to join (i.e., “chicken and egg” problem). Blockchain-enabled utility tokens hold the promise to overcome this problem. They supposedly provide a suitable financial incentive for their owners to join the platform as soon as possible. In the first half of 2018, investors seemed to believe in the presumption and spent more than US 17.6 billion in token sales. To date, we know little about this financial incentive in the context of the token economy. For this purpose, we model the token value development and the associated incentives in a multi-sided blockchain-enabled platform. The resulting findings suggest that blockchain-enabled utility tokens can help to overcome the “chicken and egg” problem. However, these tokens lead to contradictory incentives for platform participants, and can even inhibit platform usage. The contribution of our work is twofold: First, we develop one of the first models for token value development. Second, our research contributes to a deeper understanding of the utility token's financial incentive.
Keywords: G15; G23; O33; 620; Multi-sided platform; Platform adoption; Blockchain; Tokenization; Token valuation